A Comparative Epigenomic Analysis of Polyploidy-Derived Genes in Soybean and Common Bean. Issue 4 (6th July 2015) - Kim, Kyung Do; El Baidouri, Moaine; Abernathy, Brian; Iwata-Otsubo, Aiko; Chavarro, Carolina; Gonzales, Michael; Libault, Marc; Grimwood, Jane; Jackson, Scott A.
Abstract : Reference methylomes provide insights into the evolutionary role of DNA methylation in paleopolyploid genomes. Abstract: Soybean ( Glycine max ) and common bean ( Phaseolus vulgaris ) share a paleopolyploidy (whole-genome duplication [WGD ]) event, approximately 56.5 million years ago, followed by a genus Glycine -specific polyploidy, approximately 10 million years ago. Cytosine methylation is an epigenetic mark that plays an important role in the regulation of genes and transposable elements (TE s); however, the role of DNA methylation in the fate/evolution of genes following polyploidy and speciation has not been fully explored. Whole-genome bisulfite sequencing was used to produce nucleotide resolution methylomes for soybean and common bean. We found that, in soybean, CG body-methylated genes were abundant in WGD genes, which were, on average, more highly expressed than single-copy genes and had slower evolutionary rates than unmethylated genes, suggesting that WGD genes evolve more slowly than single-copy genes. CG body-methylated genes were also enriched in shared single-copy genes (single copy in both species) that may be responsible for the broad and high expression patterns of this class of genes. In addition, diverged methylation patterns in non-CG contexts between paralogs were due mostly to TE s in or near genes, suggesting a role for TE s and non-CG methylation in regulating gene expression post polyploidy. Reference methylomes for both soybean and common bean were constructed, providing resources for investigating epigenetic variation in legume crops. Also, the analysis of methylation patterns of duplicated and single-copy genes has provided insights into the functional consequences of polyploidy and epigenetic regulation in plant genomes.